The Relationship between Working Hours Flexibility and Employee Performance in Flexible and Remote Working Systems in Indonesia - Ilham Maylandi S Damanik; Meldyana Permata Abdillah; Khairunnisa Risnandar Putri; Fauzan Habib Harianja; Nayla Nazmi Fazira (ISNU Nine-Star Multidisciplinary Journal, 2026)
The development of flexible work systems and remote working encourages changes in employee work patterns in various organizations, including in the regulation of working hours. Flexibility in working hours is seen as one of the policies that has the potential to affect employee performance in the face of increasingly dynamic work demands. This study aims to examine the effect of flexible working hours on employee performance on the implementation of flexible and remote working systems in Indonesia. The research method used is a descriptive qualitative approach with a literature study method. The research data is in the form of secondary data obtained from national journal articles accessed through Google Scholar and analyzed using content analysis. The results of the study show that flexible working hours tend to have a positive influence on employee performance, especially through increased work focus, more effective time management, and reduced work stress levels. However, this influence is highly dependent on the management of organizational policies, including clarity of work rules, discipline, and supervision systems. Therefore, the implementation of flexible working hours needs to be designed in a structured manner to support the optimal improvement of employee performance.